Phytochemicals Analysis and Cytotoxicity Activity of Ethanol Extract of Litseacubeba Lour.Heartwood - M, Fujiko; A, Dalimunthe; M, Masfria (Asian Journal of Pharmaceutical Research and Development, 2020)
Objective: The purpose of this study was to determine the chemical compounds whichcontained in the ethanol extract and cytotoxic activity ethanol extract of Litseacubeba heartwood induced in T47D cells. Methods: The ethanol extract was extracted by maceration using ethanol 96% solvent. Cytotoxic activity was determined with MTT method and the IC50analyzed using SPSS 23. Results: Phytochemicals screening were showed that the ethanol extract of Litseacubeba heartwood contained steroids/triterpenoids, glycosides, alkaloids, flavonoids, saponins and tannins. The IC50of ethanol extract of Litseacubeba heartwood were 349,57 ±0,35μg/ml in T47D cells. Conclusions: Ethanol extract of Litseacubeba heartwood has activity as an anticancer to T47D cells breast cancer agents.